Approximate Solution of Nonlinear Integral Equations of the Second Kind by Using Homotopy Perturbation Method - Hasan, MM; Matin, MA (Dhaka University Journal of Science, 2017)
In this paper, we apply Homotopy perturbation method (HPM) for obtaining approximate solution of nonlinear Fredholm integral equation of the second kind. Finally, some numerical examples are provided, and the obtained numerical approximations are compared with the corresponding exact solution. Dhaka Univ. J. Sci. 65(2): 151-155, 2017 (July)